Pengaruh Motivasi Kerja, Kompetensi dan Lingkungan Kerja Terhadap Kinerja Karyawan CV Amanda Kediri Tahun 2014 - Dyah Ayu Rohmawati (Universitas Nusantara PGRI Kediri, 2019)
Human resources in the company have a very important role and function for the achievement of company goals. The company's goals will only be achieved when the employees of the company have good performance. Good and bad employee performance is influenced by several factors, some of which are work motivation, competence, and work environment. This, apparently also experienced by CV Amanda Kediri. This study aims: 1) To determine the effect of work motivation on employee performance CV Amanda Kediri. 2) To determine the effect of work competence on employee performance CV Amanda Kediri. 3) To find out the influence of the work environment on the performance of CV Amanda Kediri employees. 4) To determine the effect of work motivation, work competence and work environment on employee performance at CV Amanda Kediri. This research is descriptive of 30 samples of employees from a total population of 30 employees. The sampling technique used is purposive sampling. Analysis of the data in this study using multiple linear regression analysis using statistical tools, namely SPSS version 17. The results of the study as well as conclusions are: 1) Employee motivation has a significant effect on employee performance. 2) competence has a significant effect on employee performance. 3) The work environment has a significant effect on employee performance. 5) Motivation, competence, and work environment have a significant effect on employee performance. From these conclusions it is recommended the following: 1) because motivation, competence, and work environment have been proven to affect employee performance, CV Amanda Kediri must be able to maintain this and even improve it for the better. 2) from the results of the study, there is still an influence from variables outside those in this study, which is 10.4%, so the results of this study can be used as material for further research by including other variables other than those already included in this study.